Effect of the polymer composition on the physicochemical properties of microencapsulated fish oil using spray drying - T.K, Fahim; Sarker, Md. Zaidul Islam; Ghafoor, Kashif; Al-Juhaimi, Fahad Y.; M. A. B., Rushdi; Mandal, Uttam Kumar; Jalil, Reza-ul; Gimbun, Jolius; Amid, Mehrnoush; H., Mirhosseini (Taylor & Francis, 2015)
In this study, the effect of polymer composition on physicochemical characteristics of fish oil microcapsules produced by spray drying (180 °C) was investigated. Fish oil powders were produced using hydroxy propyl methyl cellulose (HPMC) 15 cP and HPMC 5 cP as a solid carrier and PEG 6000 as a plasticizer. The ratio of the polymer to the lipid phase influenced the reconstitution properties. Initially, it was difficult to atomize the high viscous liquid like oil-water (o/w) emulsion because HPMC itself is a very viscous polymer; however, the particle sizes of less than 60 µm were produced. Scanning electron microscopy and the amount of extracted oil from the surface revealed that HPMC 15 cP provided the highest protective and prolonged effect on the covering of fish oil. The wettability and particle density of the powder was very suitable, which improve the flow ability of the powders. All the indices of powders such as surface oil, microencapsulation efficiency and surface morphology prepared from HPMC 15 cP and HPMC 5 cP showed that the stability of the microencapsulated oil was increased and hence, increased its acceptability as alternative primary polymers.